Effect of prophylactic dextrose gel on the neonatal gut microbiome. Issue 5 (2nd December 2021) - St Clair, Sophie L; Harding, Jane E; O'Sullivan, Justin M; Gamble, Gregory D; Alsweiler, Jane M; Vatanen, Tommi
Abstract : Objective: To determine the effect of prophylactic dextrose gel on the infant gut microbiome. Design: Observational cohort study nested in a randomised trial. Setting: Three maternity hospitals in New Zealand. Patients: Infants at risk of neonatal hypoglycaemia whose parents consented to participation in the hypoglycaemia Prevention in newborns with Oral Dextrose trial (hPOD). Infants were randomised to receive prophylactic dextrose gel or placebo gel, or were not randomised and received no gel (controls). Stool samples were collected on days 1, 7 and 28. Main outcome measures: The primary outcome was microbiome beta-diversity at 4 weeks. Secondary outcomes were beta-diversity, alpha-diversity, bacterial DNA concentration, microbial community stability and relative abundance of individual bacterial taxa at each time point. Results: We analysed 434 stool samples from 165 infants using 16S rRNA gene amplicon sequencing. There were no differences between groups in beta-diversity at 4 weeks (p=0.49). There were also no differences between groups in any other microbiome measures including beta-diversity (p=0.53 at day 7), alpha-diversity (p=0.46 for day 7 and week 4), bacterial DNA concentration (p=0.91), microbial community stability (p=0.52) and microbial relative abundance at genus level. There was no evidence that exposure to any dextrose gel (prophylaxis or treatment) had any effect on the microbiome. Mode of birth, type of milk fed, hospital of birth and ethnicity were all associated with differences in the neonatal microbiome. Conclusions: Clinicians and consumers can be reassured that dextrose gel used for prophylaxis or treatment of neonatal hypoglycaemia does not alter the neonatal gut microbiome. Trial registration number: 12614001263684. Abstract : This observational study nested in an RCT of oral dextrose gel vs placebo to prevent hypoglycaemia in term infants, explores whether dextrose gel has an impact on the neonatal gut microbiome.